Implementation of the Hospital on Tablet (HoT) Health Care Service Program at Jember Pulmonary Hospital - Muhammad Yazid Hidayatullah; Selfi Budi Helpiastuti; Franciscus Adi Prasetyo (POLITICO, 2025)
The rapid advancement of information technology has transformed healthcare service delivery, fostering innovations that enhance efficiency, responsiveness, and patient-centered care. This study explores the implementation of the Hospital on Tablet program at Jember Pulmonary Hospital, an initiative designed to improve service quality, accelerate medical documentation, and strengthen communication between healthcare professionals and patients. Employing a descriptive qualitative approach, data were collected through in-depth interviews, direct observations, and document analysis. The findings indicate that the Hospital on Tablet program significantly improved operational efficiency by reducing documentation time and providing real-time access to patient information. Furthermore, it enhanced interprofessional coordination and supported timely, evidence-based clinical decision-making. Despite these advantages, several challenges remain, including limited digital literacy among healthcare workers, reliance on stable internet connectivity, and the need for continuous system maintenance and updates. Overall, the Hospital on Tablet initiative demonstrates a positive impact on healthcare service performance and organizational responsiveness. Strengthening human resource capacity and technological infrastructure is essential to ensure the program’s sustainability and scalability within the broader digital transformation of hospital services